2007
DOI: 10.1503/cmaj.061523
|View full text |Cite|
|
Sign up to set email alerts
|

Frequency of adverse events in patients with poor anticoagulation: a meta-analysis

Abstract: DOI:P atients taking anticoagulants orally over the long term have international normalized ratios (INRs) that fall outside the individual therapeutic range more than one-third of the time.1 Improved anticoagulation control reduces hemorrhagic and thromboembolic event rates. 2,3 Many studies have shown that such event rates are higher when patients' INRs are outside the therapeutic range.4-11 A study that systematically measures the proportion of hemorrhages and thromboemboli that occur when INRs are above and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 65 publications
3
78
1
2
Order By: Relevance
“…Because of their relatively narrow therapeutic window and their interaction with the diet and other drugs, VKAs require tight clinical and laboratory control, not only to maintain patients within the therapeutic interval for preventing thrombotic recurrence but also to provide adequate hemostatic potential. The percentage of time spent within the therapeutic interval is inversely related to the risk of adverse events (9 ) and must be maximized by the combined action of skilled clinical and laboratory personnel, which can be best achieved through dedicated anticoagulation clinics. Such clinics are not widely available worldwide, however.…”
Section: © 2012 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Because of their relatively narrow therapeutic window and their interaction with the diet and other drugs, VKAs require tight clinical and laboratory control, not only to maintain patients within the therapeutic interval for preventing thrombotic recurrence but also to provide adequate hemostatic potential. The percentage of time spent within the therapeutic interval is inversely related to the risk of adverse events (9 ) and must be maximized by the combined action of skilled clinical and laboratory personnel, which can be best achieved through dedicated anticoagulation clinics. Such clinics are not widely available worldwide, however.…”
Section: © 2012 American Association For Clinical Chemistrymentioning
confidence: 99%
“…[7][8][9] Clinical event rates are typically minimal when patients' international normalized ratio are within the therapeutic range, 10 but more than half of adverse events related to oral anticoagulation are directly attributable to international normalized ratio values outside the therapeutic range. 11 More than half of the adverse drug events that affect ambulatory patients occur because of inadequate monitoring, 12,13 making this aspect of care an attractive target for safety strategies. Several interventions, including the use of automated telephone messages 14 and academic detailing, 15 appear to improve physician and patient compliance with laboratory monitoring.…”
mentioning
confidence: 99%
“…Those factors may result in poor compliance with significant OAC treatment within the therapeutic range. 7, 8 Recently, clinical trials of NOACs have been completed, including dabigatran in the RE-LY trial, 9 rivaroxaban in the ROCKET-AF trial, 10 and apixaban in the ARISTOTLE trial. 11 Those trials showed non-inferiority to warfarin without the necessity of INR monitoring.…”
Section: Study Limitationsmentioning
confidence: 99%